Dialogic aspects in the Cuban novel of the 1990s - Dorado-Otero, Ángela (Colección Támesis. Monografías, 2014)
This book examines six Cuban novels that contributed to the new 'boom' in Cuban fiction of the 1990s and which subvert homogenized views of Cuban identity.